The Royal Throne of Tuan Besar in the Restoration of Kubu Kingdom: A Nasab Fiqh Perspective - Abu Bakar (Graduate Program of Pontianak Institute of Islamic Studies, 2022)
This study describes the unresolved problem of the fight for the throne in the restoration of the Kubu kingdom and reveals the underlying root causes. The description of the problem is based on historical accounts and continuous local mass media coverage related to the fight for the throne. The problem is placed in its Indonesian political context, namely Regional Autonomy Era which seeks to promote the preservation and development of local culture. Nasab fiqh (Islamic Jurisprudence concerning lineage) is used as the perspective of the review. This study explains that the Kubu restoration was hindered by the fight for the throne because the nasab (lineage) requirements were used as the sole instrument. In turn, the lineage requirement has made the issues related to Kubu throne a primordial fight among the king’s descendants. This sheds some light on the fact that the throne has high heirloom value or shared inheritance which is attached to material rights. These material rights are granted by regional autonomy which provides opportunities for the king to revive local cultural roles.